PENDUGAAN LUAS HUTAN KOTA IDEAL PADA SETIAP KECAMATAN DI KABUPATEN SUBANG BERDASARKAN KEBUTUHAN OKSIGEN - Suryadi Putra, Ega; Salampessy, Messalina L.; Sasongko, Dwi Agus (Jurnal Nusa Sylva, 2024)
Urban development often overlooks the need to ensure good environmental quality. One of the fulfillments of environmental quality is the high oxygen levels in the air. This can be fulfilled by the existence of urban forests in urban areas with an ideal area. This can be done if there is a study on the oxygen needs of urban residents and the ability of urban forests to produce oxygen. The area is compared with the ideal area according to laws and regulations. This study aims to estimate the ideal area of ​​urban forests in each sub-district in Subang Regency. Oxygen needs are calculated based on the oxygen needs of residents and motorized vehicles. . The calculation of oxygen needs considers the total population and the number of vehicles, with the latter estimated using the proportional distribution of vehicle types identified at specific location. Determination of the ideal area of ​​urban forests is calculated using the Gerarkis method. The results of the study showed that the ideal area of ​​urban forests in Subang Regency was 14,965.98 ha, still below the minimum of 10% of its area (21,655.5 ha). A total of 27 sub-districts in Subang Regency showed that the need for the ideal area of ​​urban forests was still below the minimum of 10% of its area. Meanwhile, Subang District, Pagaden District, and Sukasari District are areas that require urban forest area of ​​more than 10% of their area.